Comparative and phylogenetic analyses of the chloroplast genome reveal the taxonomy of the Morus genus - Zeng, Qiwei; Chen, Miao; Wang, Shouchang; Xu, Xiaoxiang; Li, Tian; Xiang, Zhonghuai; He, Ningjia (Frontiers in Plant Science, 2022)
Mulberry (genus Morus) is an economically important wood plant with an altered ploidy level. Different studies have recognized a variable number of Morus species. In this study, the chloroplast (CP) genome of 123 Morus varieties were de novo assembled and systematically analyzed. The 123 varieties represented seven Morus species including Morus alba, Morus nigra, Morus notabilis, Morus rubra, Morus celtidifolia, Morus serrata and Morus mesozygia. The Morus cp genome was found to be 158,969~159,548 in size with 125 genes, including 81 protein-coding, 36 tRNA, and 8 rRNA genes. 87 out of 123 Morus varieties had identical CP genome sequences represented 14 different groups, respectively, which indicated that they are maternally inherited and shared common ancestors, respectively. The CP genome of Morus genus with a quadripartite structure have two inverted repeat regions (IRs, 25,654~25,702 bp) dividing the circular genome into a large single copy region (LSC, 87,873~88,243 bp) and a small single copy region (SSC, 19,740~19,994 bp). 71 Morus varieties out of 123 had identical IRs sequences. The analysis of phylogenetic tree constructed using the complete CP genome sequences in Morus indicated that Morus is a monophyletic genus and M. alba consisted of two clade M. alba var alba and M. alba var multicaulis. The Japanese cultivated germplasms were derived from M. alba var. multicaulis. We propose that Morus genus should be classified into five species M. nigra, M. notabilis, M. celtidifolia, M. rubra and M. alba with two subspecies, including M. alba var. alba and M. alba var. multicaulis. Our findings provide a valuable resource for the study of the classification, domestication, and breeding improvement of mulberry.